The physiological responses of running at critical velocity for distance runners - Lin, J. C.; Wang, S. C. (Medicine & Science in Sports & Exercise, 1999)
This study analyzed the physiological responses of male long-distance runners (N = 20) running at critical velocity. Critical velocity was assessed on the track for 800 m, 1,500 m, and 5,000 m and on a treadmill at 11, 12, and 13 mph. Heart rate, ventilation, oxygen intake, carbon dioxide output, and blood lactate were measured during a 20-minute flat run on a treadmill at 85%, 100%, and 115% of critical velocity.